Novel evidence of Appearance for Aethina tumida Murray (Coleoptera: Nitidulidae) in Apis mellifera beehives in Colombia (2023)
The objective of the word was to evaluate circumstantial evidence in relation to the presence of Aethina tumida in Apis mellifera hives in Colombia. Field trips were carried out to diagnose and identify the presence of A. tumida, in municipalities associated with the coffee zone, isolating beetle specimens when possible, removing them from the bee colonies in the brood chamber and from fruit residues disposed near the hives. The specimens were evaluated considering morphometric parameters, on 18 variables. The presence of A. tumida was established in the towns of Dosquebradas and Pereira, Risaralda. The morphometric variables agree with the specific structure of the A. tumida specimen for the head, prothorax, pterothorax, abdomen, appendages and weight, unequivocal and differentiated characters with respect to Cychramus luteus Fabricius 1787, which evidence the presence of the etiological agent. The findings after the capture and analysis of the small beetles confirm the presence of A. tumida in Apis mellifera hives in the Colombian coffee region.